Abnormal expression of TSG-6 disturbs extracellular matrix homeostasis in chondrocytes from endemic osteoarthritis - Ning, Yujie; Zhang, Pan; Zhang, Feiyu; Chen, Sijie; Liu, Yanli; Chen, Feihong; Wu, Yifan; Li, Shujin; Wang, Chaowei; Gong, Yi; Hu, Minhan; Huang, Ruitian; et al. (Frontiers in Genetics, 2022)
Background and aims: Kashin-Beck disease (KBD) is a unique endemic osteochondropathy with unclear pathogenesis in China. T-2 toxin exposure has been identified as a significant risk factor of KBD. However, the mechanism of articular cartilage damage induced by T-2 toxin is a conundrum. We explored the role of the extracellular matrix-related gene TSG-6 in the articular chondrocyte damage process under the exposure of HT-2 toxin. Methods: TSG-6 was identified as a candidate gene by mining our previous gene expression profiling of KBD and verified by qRT-PCR and immunohistochemistry. Then, TSG-6 was silenced by RNA interference technology and overexpressed induction by TNF-α. Gradient concentrations of HT-2 toxin were added to intervene with C28/I2 chondrocytes. MTT was used to observe the proliferation and cell viability of chondrocytes, and qRT-PCR was utilized to detect the expression changes of MMP1, MMP3, MMP13, COL2A1, and proteoglycan before and after treatments for verification. Results: TSG-6 was upregulated in KBD chondrocytes at the mRNA level and upregulated in the superficial, middle, and deep zones of KBD cartilage. After TSG-6 silencing, the expression of MMP1, MMP3, MMP13, and proteoglycan was significantly decreased while COL2A1 expression was significantly increased, which was reversed after the overexpression of TSG-6 induced by TNF-α (p < 0.05). The survival rate of chondrocytes was correspondingly reduced with an increase in the HT-2 toxin concentration. Compared with the blank control group, the expression of MMPs was increased in the intervention group of HT-2 toxin, while the expression of proteoglycan and COL2A1 decreased (p < 0.05). Conclusion: The upregulation of the TSG-6 gene may play a role in promoting the damage and degradation of the extracellular matrix in KBD chondrocytes under the exposure of HT-2 toxin.